Spontaneous and experimental poisoning by Myrocarpus frondosus in cattle1 - Tineli T.R.* (2024)
© 2024 Colegio Brasileiro de Patologia Animal. All rights reserved.An outbreak of photosensitization in Holstein and Jersey cattle occurred after the passage of an extratropical cyclone in Southern Brazil. On that occasion, several trees fell, including some of the species Myrocarpus frondosus (Fabaceae family) popularly known as “gabreúva”, “cabriúna” or “gabriúna”. Five heifers consumed the leaves of this plant, and all of them became ill. The main clinical signs were decreased appetite, permanence in the water, decreased ruminal movements, dry stools, congested and icteric sclera and conjunctivae, dark urine and restlessness when exposed to the sun. One heifer showed circling, incoordination, restlessness and death six days after the onset of clinical signs. From the seventh day, three heifers showed improvement; one remained apathetic, with jaundiced mucous membranes, ulceration, and scaling on the tongue, increased respiratory rate, and fever, and died 18 days after ingestion of the plant. At necropsy, photosensitivity lesions were observed on the depigmented skin, snout, teats, and ear tip, characterized by discontinuity of the skin with the formation of crusts, inflammatory exudate associated with redness of the skin, in addition to ulceration in the mouth, snout and ventral portion of the tongue and jaundice and edema in the submandibular region. The liver was enlarged, with an orange color, full gallbladder, and wall edema. Through microscopy, liver lesions were characterized by moderate and diffuse necrosis of hepatocytes, vacuolar and centrilobular degeneration, bilirubin retention and proliferation of biliary epithelium. The literature shows no reports of M. frondosus toxicity in cattle. Experiments were carried out in cattle to clarify the possible clinical-pathological picture produced by this plant. A survey of the epidemiological data of the diagnosed spontaneous outbreak was carried out, and subsequently, three cattle received the plant’s green leaves, and a fourth received the dried leaves. After administering the plant, blood samples were collected daily for blood count, measurement of liver enzymes (gamma glutamyl transferase, alkaline phosphatase, alanine aminotransferase, aspartate transferase), bilirubin, measurement of vital parameters and liver biopsy from the onset of signs. In case of death, a necropsy was performed with collection of viscera samples for macro and microscopic evaluation. The experimental part was developed at the Laboratory of Animal Pathology, CAV-UDESC. The single dose of 33g/kg of green leaves caused severe clinical signs, while the administration of 22g/kg and 11g/kg caused mild to moderate signs of the disease. The supply of desiccated leaves in a single dose did not cause clinical manifestations. M. frondosus can be blamed as a cause of spontaneous hepatogenous photosensitization in cattle. Experimentally, the ingestion of green leaves of this plant, in doses greater than 11g/kg can lead to clinical changes, with subsequent recovery, or progress to death with severe liver damage.